2005
DOI: 10.1080/09273970500216432
|View full text |Cite
|
Sign up to set email alerts
|

Update on Chronic Progressive External Ophthalmoplegia

Abstract: Mitochondrial encephalomyopathies are clinically and genetically heterogeneous disorders. External ophthalmoplegia is the most frequent symptom. Other frequently involved tissues and organs include the retina, heart, limb muscles, peripheral and central nervous system, inner ear and endocrine system. The diagnosis is based on the finding of elevated serum lactate, the characteristic histopathological changes in the muscle biopsy, and decreased activities of mitochondrial respiratory chain enzymes. In many case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 25 publications
(27 reference statements)
0
17
0
1
Order By: Relevance
“…Although asymmetric ophthalmoplegia does occur in a minority of CPEO patients [1,7], accurate measurements of ocular motility have shown that the extent of asymmetry is very small [8]. The marked asymmetry of ophthalmoplegia in our case is therefore surprising.…”
Section: Dear Sirsmentioning
confidence: 49%
See 3 more Smart Citations
“…Although asymmetric ophthalmoplegia does occur in a minority of CPEO patients [1,7], accurate measurements of ocular motility have shown that the extent of asymmetry is very small [8]. The marked asymmetry of ophthalmoplegia in our case is therefore surprising.…”
Section: Dear Sirsmentioning
confidence: 49%
“…CPEO is characterised by bilateral ptosis and global restriction of eye movements [1]. It is the commonest ocular manifestation of the mitochondrial myopathies and can occur in isolation or with additional non-ocular features [2,3].…”
Section: Dear Sirsmentioning
confidence: 99%
See 2 more Smart Citations
“…Chronic progressive external ophthalmoplegia (CPEO) is a myopathy characterized by paralysis of extraocular muscles (reviewed in ref. 84). Age at onset is variable, with many patients first noticing bilateral ptosis in the third or fourth decade of life.…”
Section: The Clinical Phenotypes Of Mitochondrial Trna Mutationsmentioning
confidence: 99%